Coastal sand dune vegetation of Velika plaža (Montenegro) - Stešević, Danijela (Array, 2020)
Velika plaža (Ulcinj, Montenegro) is the largest sandy beach along the coast of the eastern Adriatic that still has well-developed sand-dune vegetation. Although the characterization of the flora and vegetation of Velika plaža has been addressed by many authors, knowledge on its vegetation remained poor. We made a phytosociological study of sand beach vegetation comprising both dunal and wetland areas to provide a comprehensive survey of sand dune vegetation and habitat typology of Velika plaža. Based on 149 relevés (both from literature and recent field work), and with numerical classification (Flexible beta) and ordination (Non-metric multidimensional scaling) our results show that the vegetation of Velika plaža is much more diverse than previously known. Altogether, 19 plant communities from 6 vegetation classes were identified. Among them we described two new associations: Cuscuto cesatianae-Phyletum nodiflorae and Onobrychido caput-galli-Vulpietum fasciculatae.